Williams-Beuren syndrome locus: a model of CNV affecting gene dosage and phenotypes - Osborne, Lucy (Henry Stewart Talks, 2009)
Clinical overview of WBS, Genetic basis of WBS, including the role of elastin -Mechanisms of rearrangement at the WBS locus, Occurrence and implications of inversions of the WBS region, Duplication of the WBS region, Comparison of gain and loss at the WBS locus, Genotype-phenotype relationships in WBS